Cannabis Treatment in Children with Epilepsy: Practices of Canadian Neurologists. (4th July 2020) - DeGasperis, Stephanie M.; Webster, Richard; Pohl, Daniela
ABSTRACT: Background: Medical cannabis has recently emerged as a treatment option for children with drug-resistant epilepsy. Despite the fact that many pediatric epilepsy patients across Canada are currently being treated with cannabis, little is known about the attitudes of neurologists toward cannabinoid treatment of children with epilepsy. Methods: A 21-item online survey was distributed via email to 148 pediatric neurologists working in hospitals and community clinics across Canada. Questions were related to clinical practice and demographics. Results: This survey achieved a response rate of 38% (56 Canadian neurologists). These neurologists were treating 668 pediatric epilepsy patients with cannabinoids. While 29% of neurologists did not support cannabis treatment in their patients, 34% prescribed cannabis, and 38% referred to another authorizing physician, mostly to community-based non-neurologists. The majority of neurologists considered cannabis for patients with Dravet syndrome (68%) and Lennox–Gastaut syndrome (64%) after an average of three failed anticonvulsants. Twenty-seven percent considered it for patients with idiopathic generalized epilepsy, and 18% for focal epilepsy. No neurologist used cannabis as a first-line treatment. All neurologists had at least one hesitation regarding cannabis treatment in pediatric epilepsy. The most common one was poor evidence (66%), followed by poor quality control (52%) and high cost (50%). Conclusions: The majority of Canadian pediatric neurologists consider using cannabis as a treatment for epilepsy in children. With many gaps in evidence and high patient-driven demand for cannabis therapy, this survey provides immediate information from the "wisdom of the crowd, " to aid neurologists until further evidence is available.